Developing library and information center collections - Evans G Edward; Zarnosky Margaret R (Colorado Libraries Unlimited, 2004)
This work addresses the challenges of electronic publishing and puts issues of collection development into perspective, providing a broad understanding of the collection development process. The book covers all phases of collection development-from needs
Keywords: Collection development(Libraries); Information services; United States